PERAN PERILAKU INOVATIF SEBAGAI PEMEDIASI PENGARUH KECERDASAN EMOSIONAL DAN PROFESIONALISME TERHADAP PENGAMBILAN KEPUTUSAN ANGGARAN (STUDI PADA SEKRETARIAT DAERAH KABUPATEN KENDAL) - Hariyanti , Tri Yuli; Lestari , Rohmini Indah; Albert, Albert; Savitri, Fania Mutiara (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2023)
Decision making in financial budgetary on birocrat institution is very important. This study aims to determine the factors that can improve the decision making Sekretariat Daerah Kabupaten Kendal in financial budgetary. The independent variables in this study are emotional intelligence and profesionalism and the dependent variable is decision making with inovatif behavior as a mediating variable. This study uses quantitative methods by using questionnaires to collect the required data. The sample in this study were 89 employees of Sekretariat Daerah Kabupaten Kendal. The analysis used is a structural equation model (SEM) analysis using the SmartPLS analysis tool. The results of this study indicate that the emotional intelligence and profesionalism directly affect to decision making. Inovatif behavior also affects to decision making. Emotional intelligence affect to inovatif behavior but it is not affected by profesionalism. Inovatif behavior successs as a mediating variable to mediate the influence of emotional intelligence to decision making.